Public awareness of and action towards heart attack symptoms: an exploratory study in Kuantan, Pahang, Malaysia - Alshami, Abdulkareem Mohammed; Ahmed, Abdullah Abdulmajid Abdo; Jamshed, Shazia Qasim; Fata Nahas, Abdul Rahman (2019)
Background: Awareness of symptoms and action towards heart attack (HA) are very important to reduce deaths and disability. Current study aimed to assess the awareness of symptoms and action towards HA among general public. Methods: A cross-sectional study was conducted in Kuantan from May to July 2018 to recruit 393 respondents via convenience sampling. Results: The actual proportions associated with respondents who have been aware of HA symptoms ranged from 26.35% (pain/discomfort in the jaw, neck, back) to 71.65 % (chest pain, discomfort). While 35.6% of respondents would call ambulance if they see someone suffering from HA symptoms; 82% realized ≥ 1 HA symptom, 11.5% recognized all five HA symptoms and 1.3% had excellent awareness (correct recognition of all five HA symptoms, without response “Yes” to decoy question). The odds ratios (OR) for those who have an excellent awareness of all five HA symptoms were significantly high in those who were single (OR 0.023; 95% Cl 0.001-0.594), Malay (OR 0.376; 95% Cl, 0.193-0.733), who have a history of HA among their relatives (OR 2.206; 95% CI, 0.983-4.949), who received information associated with HA (OR 7.540; 95% CI, 2.037-27.914) and those who aware that HA requires quick treatment (OR 0.176; 95% CI 0.044-0.710). Conclusion: Awareness of HA symptoms and proper action seem to be poor in Malaysia. Educational interventions to increase general awareness among the lay public, specifically in the elderly and who are at high risk for cardiovascular diseases are recommended.